Pengembangan Bahan Ajar Mata Kuliah Kalkulus Vektor untuk Meningkatkan Kemampuan Berpikir Kritis Matematis - Tutut Widiastuti Anisa (JRPM (Jurnal Review Pembelajaran Matematika), 2018)
This research aims to get the result of the development of teaching materials valid vector calculus courses and proving the effectiveness of learning. The development model that will be used to develop teaching materials in this study is Four-D Models (Model 4D). The results of the use of teaching materials in the Calculus Vector subjects are stated to be valid and effective. This valid is based on: Meet the validate content and constructs set by experts. Effective learning is stated in the following 4 things. (a) Students who use learning instructional materials developed achieve individual and classical learning, (b) The average student score in the experimental class is better than the control class, (c) The influence of students' attitudes and learning skills on abilities critical thinking, and (d) There is an increase in the ability to think critically in classes that use the development of teaching materials.